The Influence of Entrepreneurship Education on Entrepreneurial Readiness Mediated by Entrepreneurial Skills and Entrepreneurial Mindset - Pudjiastuti, Fransisca Ucik; Wardana, Ludi Wishnu; Sumanto, Agus (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the influence of entrepreneurship education on the entrepreneurial readiness of vocational high school students in Pujon District, with entrepreneurial skills and mindset as mediating variables. The results of the study indicate that entrepreneurship education positively influences entrepreneurial readiness and improves students' entrepreneurial skills through the Creative Entrepreneurship Product (PKK) subject. In addition, entrepreneurship education also positively impacts changes in entrepreneurial mindset, although this mindset has yet to increase entrepreneurial readiness directly. Entrepreneurial skills have been shown to improve students' readiness to start a business. These findings indicate the importance of entrepreneurship education in preparing a workforce ready to become entrepreneurs